EFEKTIVITAS PELAKSANAAN TEACHING FACTORY SISWA SEKOLAH MENENGAH KEJURUAN (SMK) DI SOLO TECHNOPARK - Lestari, Lestari (Jurnal Nosel, 2014)
The purpose of the research was to obtain knowledge about the effectiveness of the implementation of teaching factory vocational schools  students ( SMK ) in Solo Technopark. The results of this study showed that context aspect: (1) Implementation of the teaching factory program in accordance with the predefined of vision mission. It can be known by competency improvement gained by the way of involving students in the activities of teaching factory. so that students can feel how the direct learning such as real practice in the industry. (2) The strength of the teaching factory implementation is the planning of process, the implementation, the management and the evaluation, and the good documentation. (3) The weakness of the teaching factory activity is a delay in the production of goods (over time) due to lack of facilities and instructors which only meet half of the amount should be. Input aspect: (1) Human Resources is the main role in the implementation of the teaching factory. (2) knowledge and skills are the main capital in the teaching factory program, students are required to read measuring instruments and sheet job properly. (3) the constraints in production implementation is the teaching factory program facilities are still inadequate. Process aspect: (1) The effectiveness of implementation learning the teaching factory programs belongs to very high category indicated by the most percentage 50%. (2) the setting of implementation time and attendance belongs to the high category, with percentage acquisition 59.375%. Product aspect: (1) The results of student learning  is an valuation from the teaching factory side which is the  total value during the implementation of the teaching factory. (2) the finished product tested by the planning production, so it  product performance is worthy to be distributed.